(3QSGdI aj GdbhdfLs - (3eMeO Hf RcQjG GdnqQGRj, CHh HcQ,J (B311 (3g` s ((3eMeO Hf bWH GdWHjH s)
(3ChdgG (B:s
(3Ef CcKQ ef bGd aj hLY GdbhdfL eef bQCfG cJHge, MThgG hWhdhgG HeG jfJaY Hg aj YdGL gPG GdhLY cHjQ faY s
(3BNQgG (B:s
(3aGPG QCjJ gPg GdYdGeGJ aHGOQ Edi ESgGd GdHWf hGdRjGOI aj GdMQcI hGdMeG hGdEeSGc Yf LejY eG jfaN ChjHQO GdHWf aEf Pdc eG jfaY chfg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B377 - (3U(B397s
(3GfXQgG eY GdeQTO Qbe (B"730"s
(3aj KeGfjI YTQ HGHkGs
(3HChdgG agQS HYfGhjf GdCHhGHs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdWHs